Video-Assisted Thoracoscopic Surgery Lung Resection in United States Veterans: Trends and Outcomes versus Thoracotomy - Napolitano, Michael A.; Sparks, Andrew D.; Werba, Gregor; Rosenfeld, Ethan S.; Antevil, Jared L.; Trachiotis, Gregory D. (The Thoracic and Cardiovascular Surgeon, 2021)
Background Video-assisted thoracoscopic surgery (VATS) offers reduced morbidity compared with open thoracotomy (OT) for pulmonary surgery. The use of VATS over time has increased, but at a modest rate in civilian populations. This study examines temporal trends in VATS use and compares outcomes between VATS and OT in the Veterans Health Administration (VHA).Methods Patients who underwent pulmonary surgery (wedge or segmental resection, lobectomy, or pneumonectomy) at Veterans Affairs centers from 2008 to 2018 were retrospectively identified using the Veterans Affairs Surgical Quality Improvement Project database. The cohort was divided into OT and VATS and propensity score matched, taking into account the type of pulmonary resection, preoperative diagnosis, and comorbidities. Thirty-day postoperative outcomes were compared. The prevalence of VATS use and respective complications over time was also analyzed.Results A total of 16,895 patients were identified, with 5,748 per group after propensity matching. VATS had significantly lower rates of morbidity and a 2-day reduction in hospital stay. Whereas 76% of lung resections were performed open in 2008, nearly 70% of procedures were performed using VATS in 2018. While VATS was associated with an 8% lower rate of major complications compared with thoracotomy in 2008, patients undergoing VATS lung resection in 2018 had a 58% lower rate of complications (p < 0.001).Conclusions VATS utilization at VHA centers has become the predominant technique used for pulmonary surgeries over time. OT patients had more complications and longer hospital stays compared with VATS. Over the study period, VATS patients had increasingly lower complication rates compared with open surgery.
Keywords: thoracoscopy; VATS; database; outcomes